1994
DOI: 10.1111/j.1751-1097.1994.tb05102.x
|View full text |Cite
|
Sign up to set email alerts
|

Afloqualone Photosensitivity. Immunogenicity of Afloqualone‐photomodified Epidermal Cells

Abstract: Afloqualone (AQ) is an oral muscle relaxant and evokes ultraviolet A (UVA)-induced photosensitivity dermatitis as a side effect. Histologic observations of the skin eruption suggest that AQ photosensitivity is mediated not only by phototoxic but also by photoallergic mechanisms. To address the immunological mechanisms of AQ photosensitivity, we examined the immunogenicity of AQ-photomodified epidermal cells in mice. Afloqualone was covalently coupled with bovine serum albumin by irradiation with UVA but not UV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
42
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(44 citation statements)
references
References 13 publications
2
42
0
Order By: Relevance
“…The phototoxicity is mediated by reactive oxygens, in particular singlet oxygen [11], while the photoallergenicity occurs as a consequence of immunological events, where the UVinduced formation of photoantigen triggers T cell responses [8][9][10]. Recently, the incidence of the photoallergic type is higher than that of the phototoxic one [1,6,7]. Our studies have suggested that the vast majority of clinically photoallergic chemicals are photohaptens that bind covalently to protein under exposure to UV [1,6,7,9].…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations
“…The phototoxicity is mediated by reactive oxygens, in particular singlet oxygen [11], while the photoallergenicity occurs as a consequence of immunological events, where the UVinduced formation of photoantigen triggers T cell responses [8][9][10]. Recently, the incidence of the photoallergic type is higher than that of the phototoxic one [1,6,7]. Our studies have suggested that the vast majority of clinically photoallergic chemicals are photohaptens that bind covalently to protein under exposure to UV [1,6,7,9].…”
Section: Introductionmentioning
confidence: 90%
“…Recently, the incidence of the photoallergic type is higher than that of the phototoxic one [1,6,7]. Our studies have suggested that the vast majority of clinically photoallergic chemicals are photohaptens that bind covalently to protein under exposure to UV [1,6,7,9].…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…In general, photoreactions by photosensitive chemicals are divided into the phototoxic and photoallergic types. While phototoxicity is mediated by active oxygen, especially singlet oxygen [8,9], photoallergy occurs as a consequence of a specific immune reaction mediated by antigenspecific, sensitized T cells [10][11][12][13][14]. KP has both phototoxic and photoallergic potentials, but many clinical observations have indicated that photosensitivity to KP is a photoallergic reaction [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 98%